Presence, self awareness and self care in professionals working with suffering - Benito Oliver, Enrique (2020)
Professionals working in a sanitary environment are often exposed to high emotional experiences that rise from the contact with vulnerability, loss, and suffering of patients and relatives, leading to a high exposition to stress.Advances in neurobiology and a higher knowledge of therapeutic relationships allow a better understanding of how we can look after ourselves better and provides resources to transform the experience of sufferers and companions.Understanding the role of self-awareness, presence and self-care and their neurobiological fundamentals allow the development of proposals to prevent the risk of burnout and other prevalent mental health problems among professionals.This work reviews the basis of help relationship, the risks and chances of our work, the relationship between empathy, self-awareness and compassion, as well as the emotional balance needed to work in this environment and self-awareness as a platform of presence and emotional regulation.Some useful practices for selfcare are presented, including teamwork as a protection factor. Finally, a commitment of professionals with their self-care is proposed.